LES DETERMINANTS DE CHOIX D’UN PRODUIT ETRANGER ET L’IMPACT DE L’ORIGINALITE DU PRODUIT DANS LE CADRE DES ACCORDS DE LIBRE ECHANGE SUR LE CONSOMMATEUR : CAS DU MATERIEL AGRICOLE - Kaissouni, Hicham (European Scientific Journal, ESJ, 2014)
The evolution of international markets and the opening of new fast growing markets, particularly at the regional level, offer many opportunities that require the adoption of new international marketing strategies. Changes in the international market require studying the effects of the country’s image and the effects of all psychological variables and consumer graphics, as patriotism, animosity and openness to foreign cultures, on the assessment of foreign products and purchasing intent of consumers. This research that we begin here is nothing other than the result of previous work in various aspects and dealing with disparate paradigms. However, the fundamental link between this works would be that the definition of a standard behavior of producers in the face of an evolving and changing consumer behavior and the definition of consumption values of the made in [P. GABRIEL, B. URIEN, 2006]. It treats also the representation that a consumer is forming, based on social and cultural referents, about the country of origin as an indicator of product quality.